Impact of background utilization and background traffic on the foreground applications in a wide area network - Uddin, Zia; Kim, Jongmyon (© 2012 Springer Science+Business Medi, 2016)
This conference paper was presented in the 4th FTRA International Conference on Computer Science and Its Applications, CSA 2012; Jeju Island; South Korea; 22 November 2012 through 25 November 2012 [© 2012 Springer Science+Business Media] The conference paper's definite version is available at: :http://dx.doi.org/10.1007/978-94-007-5699-1_92